Synthesis of tubular ZIF-8 membranes for propylene/propane separation under high-pressure - Li, Jinfu; Lian, Haiqian; Wei, Kaifeng; Song, Eryue; Pan, Yichang; Xing, Weihong (Journal of membrane science, 2020)
ZIF-8 membrane-based separation of propylene/propane is attractive for reducing the energy and cost of the conventional cryogenic distillation. However, the high-pressure permeation results are rarely reported on the tubular ZIF-8 membranes. In this work, high-quality ZIF-8 membranes were successfully fabricated on the tubular ceramic support. The coating of a PDMS layer can significantly improve the quality and reproducibility of as-synthesized membranes. The effect of permeating temperature (35–100 °C) and feeding pressure (1~6 bar) as well as the feeding compositions on the C3H6/C3H8 separation performance are carefully investigated. The C3H6/C3H8 permeation manners (with or without sweep gas, and under vacuum) on the tubular ZIF-8 membrane are also compared. Concentration polarization is only obviously existed when no sweep gas is used. [Display omitted] •High quality ZIF-8 membranes supported on commercial tubes were fabricated.•High reproducibility of as-synthesized membranes is achieved by a PDMS coating.•C3H6/C3H8 permeation performances under high pressure were carefully investigated.•Different permeation manners of C3H6/C3H8 on ZIF-8 membranes were evaluated.